Linux Command line essentials. (Manning Publications, 2022)
This course is designed for people who want to develop command line skills on the Linux operating system and need to do it in a short period of time. By the end of the course you will be able to easily navigate your way around a Linux system and feel confident at the command line. As an added bonus for enrolling in the Linux Command Line Essentials video training course, you'll receive a cheat sheet and reference card that lists the most important Linux commands you'll need to know. It's a great way to quickly review what you've learned in this course AND you'll be able to easily find the command and options you're looking for too. What you learn in Linux Command Line Essentials applies to any Linux environment including Ubuntu, Debian, Linux Mint, RedHat, Fedora, OpenSUSE, Slackware, and more.